Retroperitoneal Lymphangioma in an Adult: A Case Report of a Rare Clinical Entity - Mayank Tripathi; Sanjeev Parshad; Rajender Kumar Karwasra; Ashish Gupta; Saket Srivastva; Ankush Sarwal (Case Reports in Surgery)
Background. Retroperitoneal lymphangioma is a rare, benign mesodermal tumor arising from the retroperitoneal lymphatics which usually presents in infancy and it is worthy to report a case when it has presented in an adult. After a thorough literature search in English we concluded that less than 200 cases of adult retroperitoneal lymphangioma have been reported so far. Apart from being a rare entity it also presents as a diagnostic dilemma and final diagnosis is often made on surgical exploration. Case Presentation. We report a case of retroperitoneal lymphangioma in a 55-year-old male who presented with abdominal distension and dull aching abdominal pain. Conclusion. Retroperitoneal lymphangiomas are rare tumors of infancy but may also present in adults where they are a diagnostic challenge. Differentiating cystic lymphangiomas from other cystic growths by imaging studies alone are often inconclusive and surgery is frequently required for definitive diagnosis and to ameliorate the symptoms.